Konsentrasi Industri Berdasarkan SCP (Structure-Conduct-Performance) - Meila Farhatus Soliha; Kangza Ardila; Salsabila Nur ‘Aifa; Iqbal Asyraf Junius; Naerul Edwin Kiky Aprianto (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The market will continue to undergo changes, as well as the industrial market, so as to enable the perpetrators of the industry to persevere in the midst of market competition, to determine market structures, can be used a method often referred to as an industrial concentration. This is often the case in the midst of economic turmoil, with the industrial concentration based on SCP (Structure-Conduct-Performance) of the problems associated with market conditions and structure will be predicted. This study deals with the understanding, insight, and concept of industrial concentration. The method used is qualitative descriptive. The purpose of this research is to analyze industrial concentration as one part of the economic substance.